Gene therapy strategies for X-linked myotubular myopathy. (4th March 2018) - Pierson, Christopher R.
ABSTRACT: Introduction : X-linked myotubular myopathy (XLMTM) is a severe, frequently fatal, type of congenital myopathy for which only supportive care is currently available. XLMTM is due to MTM1 mutations that lead to a deficiency in myotubularin, a lipid phosphatase. Restoring functional myotubularin expression in skeletal muscle would be the most direct approach to treat XLMTM. Recent work in gene therapy using animal models has revealed exciting, clinically meaningful results. Areas covered : Gene therapy using skeletal muscle trophic adenoassociated virus 8 (AAV8) as a vector has shown promise to safely deliver MTM1 and restore myotubularin expression, which improves muscle function, ameliorates pathology and considerably lengthens survival over time. The XLMTM dog has provided a large animal model for these experiments, which has enhanced their value and our ability to move toward implementing gene therapy into XLMTM clinical care. An overview the progress that has been made will be provided here. Expert opinion : A variety of approaches have been applied to treat XLMTM, but gene therapy appears to be the most efficient and direct means to safely restore myotubularin expression in XLMTM skeletal muscle. Future efforts will focus on ensuring the safety of gene therapy vectors while developing clinically relevant dosing regimens.